Group psychotherapy to treat patients with schizophrenia hospitalized in public health services - Josefina Bestard Ricoy; Martha Beatriz Cutiño Segura (Centro Provincial de Información de Ciencias Médicas, 2019)
The necessity of comprehensive care to the patient with schizophrenia hospitalized in public health services in all its levels, including the cultural and the spiritual one is stated. In the care at psychological level, brief psychotherapy of institutional group is proposed, which is directed to the solution of problems at short term "here and now", with the use of resources based on the effect of the word, the didactic-inspirative effect, as well as others according to the necessities of the sick persons. From the hospital admission the patient will be offered emotional support. It is recommended to give care at this level with individual sessions of psychotherapy, family interventions, occupational therapy and social work. At discharged, care should be continued to this sick person in the mental health centers.